Analisis Kemampuan Berpikir Kritis : Eksperimen Model Pembelajaran Jucama Berbantuan MMS Berdasarkan Self-Confidence - Sari, Dewi Nevita; Nabila, Siti Ulfa; Anggoro, Bambang Sri (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
Mathematics learning requires the ability to think at a high level, including the ability to think critically. However, in Indonesia, this ability still requires further development. This ability can be developed through the use of models that orient students to always be involved in submitting and solving problems, and using media that can support learning. The purpose of this study was to investigate the effect of the ability to think critically taught by the JUCAMA model, the JUCAMA model using MMS and the expository model by considering the influence of self-confidence. The approach applied in this study was quantitative in the type of quasi-experiment and samples, namely 2 experimental classes and 1 control class, and using a two-way ANOVA test for data analysis. The findings of this study: (1) the application of the JUCAMA model contributes to the influence of students' ability to think critically, (2) the JUCAMA model using MMS assistance contributes to the influence of berfikir kritis skills, (3) self-confidence is able to influence students' ability to think critically, (4) there is no interaction between self-confidence and the JUCAMA model in influencing students' ability to think critically, (5) there is no interaction between the JUCAMA model using MMS assistance and self-confidence in influencing berfikir kritis skills.